1990
DOI: 10.1097/00006842-199005000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in hemodynamic responses to the cold face stimulus in children and adults.

Abstract: The prevalence of essential hypertension is higher among blacks than whites. One reason for this difference may be that blacks are more reactive to stressors that produce vasoconstrictive responses. Two studies were conducted to test this hypothesis, one with 10- to 14-year-old males (20 whites, 20 blacks) and one with young adult males (10 whites, 10 blacks). Subjects had blood pressure, heart rate, cardiac output, and total peripheral resistance measured before, during, and after exposure to forehead cold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
49
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 0 publications
8
49
0
Order By: Relevance
“…- 43 These studies differ from the exercise studies mentioned above in that blacks did not exhibit higher resistance values at rest. In either case, it is apparent that racial differences in BP during physical stress result from an elevated vascular resistance in blacks compared with whites.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…- 43 These studies differ from the exercise studies mentioned above in that blacks did not exhibit higher resistance values at rest. In either case, it is apparent that racial differences in BP during physical stress result from an elevated vascular resistance in blacks compared with whites.…”
mentioning
confidence: 59%
“…43 The black subjects demonstrated an elevation in TPR both at rest and during exercise. An elevation in TPR would have a more pronounced effect on MABP during exercise than at rest.…”
mentioning
confidence: 92%
“…Previous studies have demonstrated that elevated vascular reactivity (ie, DBP reactivity and vascular resistance) is more prevalent among blacks than whites. 3,[31][32][33][34] Furthermore, it has been demonstrated that total peripheral resistance and norepinephrine responses to stress are greater in offspring of hypertensive than normotensive individuals. 35,36 These studies suggest that the presence of preclinical changes in vascular reactivity are most likely linked to heightened sympathetic nervous system activity.…”
Section: Discussionmentioning
confidence: 99%
“…Each child then participated in the cold face stimulus procedure. 21 Before the task, subjects relaxed for a 10-minute period. Next, 4 baseline SBP, DBP, and HR measures were obtained by a trained technician.…”
Section: Cvr Testingmentioning
confidence: 99%